2018
DOI: 10.3102/0162373718769379
|View full text |Cite
|
Sign up to set email alerts
|

Pulling Back the Curtain: Revealing the Cumulative Importance of High-Performing, Highly Qualified Teachers on Students’ Educational Outcome

Abstract: This study examines the relationship between two dominant measures of teacher quality, teacher qualification and teacher effectiveness (measured by value-added modeling), in terms of their influence on students’ short-term academic growth and long-term educational success (measured by bachelor’s degree attainment). As students are exposed to teachers of varying quality over the course of their schooling, this study computes cumulative teacher quality indices that are able to more precisely estimate the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 73 publications
(70 reference statements)
1
46
0
2
Order By: Relevance
“…Only in the last few years have a series of studies emerged examining the "cumulative and chronic adverse effects" that make structural racism so pervasive and hard to eliminate (Lawrence & Keleher, 2004, p.1). Using the Longitudinal Study of American Youth (LSAY) conducted from 1987-1994, Lee (2018) and Lee and Mamerow (2019) determined that students exposed to a series of more experienced and more effective teachers had higher short-and long-term educational success. Using more recent data, Goldhaber et al (2018) found that gaps in teacher quality existed across time in both North Carolina and Washington State, with the largest gaps between race, not poverty level.…”
Section: An Investigation Of Teaching Experience Across Racial Groupsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only in the last few years have a series of studies emerged examining the "cumulative and chronic adverse effects" that make structural racism so pervasive and hard to eliminate (Lawrence & Keleher, 2004, p.1). Using the Longitudinal Study of American Youth (LSAY) conducted from 1987-1994, Lee (2018) and Lee and Mamerow (2019) determined that students exposed to a series of more experienced and more effective teachers had higher short-and long-term educational success. Using more recent data, Goldhaber et al (2018) found that gaps in teacher quality existed across time in both North Carolina and Washington State, with the largest gaps between race, not poverty level.…”
Section: An Investigation Of Teaching Experience Across Racial Groupsmentioning
confidence: 99%
“…More often than not, these lower non-special education tracks (standard), populated with disproportionately Black and Latino students, are much more likely to be taught by unlicensed, inexperienced instructors who are teaching outside of their field (Lee, 2018;Lee & Mamerow, 2019;). Mickelson (2001) notes, Among the CMS high school principals I interviewed about tracking, race, and opportunities to learn, the consensus is that students in the lower tracks may have fully licensed and experienced teachers with advanced degrees, but those in the highest tracks always do.…”
Section: Second-generation Segregation: Ability Grouping and Resourcementioning
confidence: 99%
See 2 more Smart Citations
“…36 See, e.g.,Taylor and Rohrer (2010). 37 See a comprehensive review inHanushek and Rivkin (2006).38 See, e.g.,Lee (2018),Hanushek et al (2019) and the references therein.8 Curriculum and Educational Reforms in Portugal: An Analysis on Why and How……”
mentioning
confidence: 99%